Perlaksanaan PdPC Balaghah Di Institusi Pengajian Tinggi Dari Perspektif Pensyarah - Yuslina Mohamed; Mohamed Haji Ibrahim; Nurhasma Muhammad Saad; Sulaiman Ismail; Ab Adly Rabbanie Ab Rahim (Arabic Language Programme, Faculty of Islamic Stud, 2024)
AL-QALAM International Online Journal of Arabic Language Studies Faculty of Islamic Studies, National University of Malaysia https://www.ukm.my/alqalam/ Vol. 1 No. 1 (2021)